Learner engagement in a MOOC in the Arab world: A case study analysis using the community of inquiry framework - Aboulmagd, Nadine (AUC Knowledge Fountain, 2018)
Massive Open Online Courses (MOOCs) have been offered by many institutions around the globe for the better part of a decade, and more recently in the Arab World. Learner engagement in MOOCs has also been researched in attempts to explain the varying degrees of engagement in these courses. This research aimed to explore the factors that affect learner engagement using an Arabic MOOC about E-Marketing offered by Edraak, one of the leading MOOC providers in the region, as a case study. This study used a mixed methods approach to explore the significance of the relationship between a) learner engagement and multiple demographic and psychographic variables of learners, and b) learner engagement and the perception of learners about the Community of Inquiry (CoI) presences; teaching presence, social presence and cognitive presence. Additionally, the research included interviews with some of the learners who participated in the MOOC in order to better understand the factors they themselves attribute to their engagement or disengagement; aiming to also explore the relationship between their engagement levels and their motivations, intentions from enrolling in the MOOC and self-regulated learning strategies. This study used a Chi-square test to explore which variables and presences had statistically significant relationships with engagement, which was defined as the level of learner interaction with the course activities, namely watching the weekly videos and attempting to solve the weekly quizzes. The results of the Chi-square test as well as a thematic analysis of the interviews using the CoI model, theories of motivation, self-regulated learning and andragogy are presented. Results of Chi-square test indicated that there is in fact statistical significance between learner engagement and variables such as age group, goal from enrolling in the MOOC, knowledge about the MOOC subject, eligibility for receiving a course completion certificate, previous enrollment in MOOCs and self-motivation. There was no statistical significance observed between the level of learner engagement and their perceptions of the CoI presences. A discussion on the interpretation of this data, the study limitations as well as recommendations for future research is also presented.